2016
DOI: 10.1542/hpeds.2015-0138
|View full text |Cite
|
Sign up to set email alerts
|

Description and Evaluation of an Educational Intervention on Health Care Costs and Value

Abstract: A B S T R A C T OBJECTIVE:There is growing consensus that to ensure that health care dollars are spent efficiently, physicians need more training in how to provide high-value, cost-conscious care. Thus, in fiscal year 2014, The Children's Hospital of Philadelphia piloted a 9-part curriculum on health care costs and value for faculty in the Division of General Pediatrics. This study uses baseline and postintervention surveys to gauge knowledge, perceptions, and views on these issues and to assess the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Finally, our survey supports the fact that targeting faculty-and attending-level providers for HVC education efforts may be important in addition to cost transparency, as both were identified as key barriers to performing HVC. There has already been a successful effort in pediatrics to train attending-level providers on cost, 26 and spreading this effort to other areas may yield positive results. Institutions that only target trainees for HVC education risk creating conflict between this formal curriculum and the informal or ''hidden'' curricula we often see in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our survey supports the fact that targeting faculty-and attending-level providers for HVC education efforts may be important in addition to cost transparency, as both were identified as key barriers to performing HVC. There has already been a successful effort in pediatrics to train attending-level providers on cost, 26 and spreading this effort to other areas may yield positive results. Institutions that only target trainees for HVC education risk creating conflict between this formal curriculum and the informal or ''hidden'' curricula we often see in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Lectures were adapted from a previously described faculty development curriculum. 30 Topics include an introduction to value in health care, health care costs, balancing cost with other important factors in health care, and high-value diagnosis. Key objectives are used to address comprehension, knowledge, and application.…”
Section: Educational Strategiesmentioning
confidence: 99%
“…Quantitative data collection occurred via an anonymous, voluntary REDCap (Research Electronic Data Capture) 32 survey adapted from a previously published tool (see Supplemental Fig 3 for the complete tool), 10,30 and the survey was distributed to all residents before initiation of the curriculum in July 2016 and after exposure to the curriculum in May 2017 (6 months after completion of lecture series).…”
Section: Evaluation Of the Curriculummentioning
confidence: 99%
“…The Children' s Hospital of Philadelphia recently piloted a multipart curriculum for general pediatricians and found that it improved HVCCC knowledge and perceptions, although change in actual practice was not assessed. 17 Although the literature is not entirely conclusive, a 2015 systematic review showed that presenting charge data to physicians generally changed ordering practices without impacting the quality of care. 18 Because transparency about pricing data is highly variable, publicly available websites such as the California Chargemaster and Healthcare Bluebook may provide useful surrogate materials for programs.…”
Section: Discussionmentioning
confidence: 99%